Comparing the perception of family-centered care from the perspectives of nursing staff and mothers of hospitalized children in children's wards - Azar Aran; Farokh Abazari; Jamileh Farokhzadian; Mansooreh Azizzadeh Forouzi (Tehran University of Medical Sciences, 2018)
Background & Aim: Family-centered care is a concept for describing the approach to caring for children and their families in health services and its main element is the involvement of parents in child care. This study aimed to compare the perception of family-centered care from the perspectives of nursing staff and mothers of hospitalized children in children's wards. Methods & Materials: This study was a cross-sectional study conducted on 82 mothers of hospitalized children and 60 nurses working in children's wards of Afzalipour hospital in Kerman in 2017. In this study, a questionnaire on the family-centered care perception from the perspectives of nurses and mothers was used for data collection. Data were analyzed through SPSS software version 20 using t test, analysis of variance and Pearson correlation coefficient. Results: Average scores for the perception of family-centered care from the perspective of nurses (3.17±0.79) and of the mothers (2.47±0.85) had significant differences between the two groups (P<0.001). In two groups, the highest average was related to the area of cooperation and the lowest average was related to the support area. Conclusion: Findings showed nurses' and mothers' perceptions of family-centered care were positive but nurses have significantly more positive perception than mothers. This can be promising and nursing staff are required to be diligent about mothers' participation in care so that the child receives better care.